CURRENT THERAPY OF REPEAT BREEDING IN CROSS-BRED DIARY COWS WITH DILUTED POVIDONE IODINE - Omer Ahmed, Faisal; Salim Elsheikh, Adil; Abdalla Homeida , Abdelrahim (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to examine treatment of repeat breeder (RB) dairy cows with diluted Povidone iodine (2%). Sixty cross-bred dairy cows suffer repeat breeding were used to investigate the efficacy of intra-uterine infusion of diluted Pvidone iodine for treatment of repeat breeding in dairy cows. Uterine swabs were collected from uteri of the candidate cows prior treatment. After bacterial culture the uteri of the selected cows were found mildly infected (subclinical endometritis). They were then divided randomly into three equal groups. Group A (n = 20 cows) was intra-uterine infused with 2% Povidone iodine 6 hours pre-insemination. Group B (n = 20 cows) was infused with the same solution 6 hours post-insemination. Group C (n = 20 cows) was left without treatment to serve as control. The potency and efficacy of diluted Povidone iodine to cure repeat breeding in dairy cows was evaluated by studying three parameters, the days open (DO), rate of service per conception and the calving interval (CI). The results of this study revealed that, the DO, rate of service per conception and CI were significantly (P<0.001) reduced by intra-uterine infusion of diluted Povidone solution 6 hours pre and post insemination as compared to the control. It is concluded that, the repeat breeding (RB) syndrome in cross-bred dairy cows is most likely to be due to sub-clinical endometritis of the reproductive tract as well as deficiency of Iodine. Furthermore, intra-uterine infusion of 2% Povidone iodine can be used successfully to improve the reproductive efficiency of RB dairy cows